Psychological Integration and Its Relationship with Certain Offensive Skills in Basketball Among Students - Ahmed Mahmood Mahdi (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
This study aims to develop a psychological integration scale for students at the College of Physical Education and Sports Sciences, assess their level of psychological integration, and determine the type of correlational relationship between psychological integration and certain offensive basketball skills. The researcher employed survey and correlational approaches within a descriptive method. The research population consisted of thirty male and female fourth-year students enrolled in the morning study program at the University of Samarra's College of Physical Education and Sports Sciences during the 2024-2025 academic year. The sample was selected randomly and comprised fifteen male and female students. The psychological integration scale was applied to the sample, along with tests measuring three offensive basketball skills: high dribbling, chest pass, and set shooting. Data were analyzed using appropriate statistical methods including arithmetic mean, standard deviation, and Pearson's simple correlation coefficient. The results revealed: (1) a high level of psychological integration among the students, and (2) a statistically significant correlational relationship between psychological integration and the performance of certain offensive basketball skills among students.